Tratamento químico de sementes de milho e o teste de condutividade elétrica - Vazquez, Gisele Herbst [UNESP]; Cardoso, Renata Danielle; Peres, Amanda Ribeiro [UNESP] (Univ Federal Uberlandia, 2014)
In different crops, the seeds treatment with the use of fungicides and/or insecticides has been performed before the storage or in the seeding moment as a guarantee form of longer conservation period and adequate initial stand. However, it is not known if the various products used for the treatment interfere with test results of electrical conductivity of corn seeds. The experimental design was completely randomized and the analysis carried out in a factorial 5x5x2 with four replications. The treatments consisted of five cultivars of corn (DKB 390YG, DKB 185YG, 2B710, AGN-30A91HX and AL Bandeirante) treated with four insecticides (imidacloprid+thiodicarbe, thiamethoxam, fipronil, fipronil+piraclostrobin+thiophanate-methyl), and the control previously treated by the company with fungicides (fludioxonil+metalaxyl-M e captan) and insecticides (pirimiphos-methyl, deltamethrin e bifenthrin), analyzed in two different times (after treatment and at 35 days of storage). Seeds were subjected to tests of germination, electrical conductivity and water content. The results showed that the treatment of corn seeds with insecticides and fungicides doesn't interfere on the test results of electric conductivity, even if the analysis is made after 35 days of storage of seeds.

Em diversas culturas, tem sido efetuado o tratamento com fungicidas e/ou inseticidas antes do armazenamento das sementes ou no momento da semeadura, como forma de garantia de maior período de conservação e adequado estande inicial. Todavia, existem dúvidas se os produtos utilizados para o tratamento químico interferem no resultado do teste de condutividade elétrica de sementes de milho. Foi empregado o delineamento experimental inteiramente casualizado e os tratamentos dispostos em esquema fatorial 5 × 5 × 2 com quatro repetições. Os tratamentos foram constituídos por cinco cultivares de milho (DKB 390YG, DKB 185YG, 2B710, AGN-30A91HX e AL Bandeirante) tratados com quatro inseticidas (imidacloprid+thiodicarbe, thiamethoxam, fipronil, fipronil+piraclostrobyn+thiophanate-methyl), além da testemunha já previamente tratada pela própria empresa com fungicidas (fludioxonil+metalaxyl-M e captan) e inseticidas (pirimiphos-methyl, deltamethrin e bifenthrin), analisados em duas épocas (após o tratamento e aos 35 dias de armazenamento). As sementes foram submetidas aos testes de germinação, condutividade elétrica e à determinação do teor de água. Os resultados permitem concluir que, o tratamento de sementes de milho com os inseticidas e os fungicidas testados não interfere no teste de condutividade elétrica, mesmo que a análise seja efetuada após 35 dias de armazenamento das sementes.
Chemical treatment of corn seeds and the result of the electrical conductivity test
Keywords: Zea mays; Vigor test; Insecticide; Fungicide